eIF2α confers cellular tolerance to S. aureus α-toxin - von Hoven, Gisela; Neukirch, Claudia; Füser, Sabine; Bidna Petrivna, Maria; Meyenburg, Martina; Rivas, Amable J.; Ryazanov, Alexey; Kaufman, Randal J.; Aroian, Raffi V.; Husmann, Matthias (Frontiers in Immunology, 2015)
We report on the role of conserved stress-response pathways for cellular tolerance to a pore formingtoxin. First, we observed that small molecular weight inhibitors including of eIF2α-phosphatase, jun-N-terminal kinase (JNK), and PI3-kinase sensitized normal mouse embryonal fibroblasts (MEFs) to the small pore forming S. aureus α-toxin. Sensitization depended on expression of mADAM10, the murine ortholog of a proposed high affinity-receptor for α-toxin in human cells. Similarly, eIF2αS51A/S51A MEFs, which harbor an Ala knock-in mutation at the regulated Ser51 phosphorylation site of eukaryotic translation initiation factor 2, were hyper-sensitive to α-toxin. Inhibition of translation with Cycloheximide did not mimic the tolerogenic effect of eIF2α-phosphorylation. Notably, eIF2α-dependent tolerance of MEFs was toxin-selective, as wild type-MEFs and eIF2αS51A/S51A MEFs exhibited virtually equal sensitivity to Vibrio cholerae cytolysin. Binding of S. aureus α-toxin to eIF2αS51A/S51A MEFs and toxicity in these cells were enhanced as compared to wild type cells. This led to the unexpected finding that the mutant cells carried more ADAM10. Because basal phosphorylation of eIF2α in MEFs required amino acid deprivation-activated eIF2α-kinase 4/GCN2, the data reveal that basal activity of this kinase mediates tolerance of MEFs to α-toxin. Further, they suggest that modulation of ADAM10 is involved. During infection, bacterial growth may cause nutrient shortage in tissues which might activate this response. Tolerance to α-toxin was robust in macrophages and did not depend on GCN2. However, JNKs appeared to play a role, suggesting differential cell type- and toxin-selectivity of tolerogenic stress-responses. Understanding their function or failure will be important to comprehend anti-bacterial immune responses.